Therapeutic potentials of endophytes for healthcare sustainability. Issue 1 (1st January 2021) - Falade, Ayodeji O.; Adewole, Kayode E.; Ekundayo, Temitope C.
ABSTRACT: Morbidity and mortality rates are on the upward trajectory globally, probably due to lack of effective treatments and poor healthcare. Most effective drugs are, however, characterized by serious side effects upon long usage. It is, therefore, imperative to explore natural sources for efficient therapeutics with little or no side effects. This paper outlines the therapeutic potentials of endophytes using published articles on endophytes in both Web of Science (WoS) and Scopus (1990–2020). Scientific evidences discussed in this review suggest endophytic microbes as reservoirs of novel bioactive compounds belonging to the following classes alkaloid, xanthones, methoxyphenols, depsipeptide, bicyclic lactones, depsidoenes, butenolides, maleimide-bearing compounds, ergosterol, spirobisnaphthalenes, benzopyran derivatives, isofuranonaphthalenone, butyrolactones, diketopiperazine, sesquiterpenoids, cytochalasin-related compounds, pestalols and cyclic pentapeptides. The identified compounds are characterized by promising therapeutic potentials such as antioxidant, anti-inflammatory, antimicrobial, anticancer, antidiabetic, antiviral, neuroprotective, and hepatoprotective properties, which are significant to healthy living and sustainable healthcare. This review further discusses the emerging potentials of endophytes in the production of antibiofilm, anti-multiresistant Staphylococcus aureus (anti-MRSA) and lipase inhibitors (LIs). The prospective applications of endophytes in the development of anti-COVID-19 medications and therapeutics for the management of neglected tropical diseases (NTDs) are also advocated in this review. The therapeutic potentials of endophytes, if properly harnessed, would in no small measure contribute to good health, which is an integral part of the sustainable development goals (SDGs) of the United Nations (UN).